DOMESTIC VIOLENCE IN INDIA: A CRITICAL ANALYSIS OF THE CRIMINAL JUSTICE SYSTEM AND LEGAL RESPONSES - Mirza, Raheen; Matolia, Manisha (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Domestic abuse constitutes a significant and enduring infringement of human rights in India, impacting individuals from diverse social, economic, educational and cultural backgrounds. It encompasses physical, emotional, psychological, sexual and economic abuse occurring inside domestic relationships, primarily targeting women. Notwithstanding constitutional assurances of equality and dignity, together with the implementation of specific legislation like the Protection of Women from Domestic Violence Act, 2005, domestic violence is pervasive in Indian society. The enduring nature of this issue is primarily shaped by patriarchal social institutions, female inequality, social stigma, economic dependency, insufficient awareness and inadequate enforcement of legal laws. This article analyzes the characteristics, origins and prevalence of domestic violence in India and assesses the efficacy of the criminal justice system in addressing these offenses. It examines the function of diverse institutions, including as law enforcement, the judiciary, protection officers, legal aid organizations and social welfare agencies, in safeguarding and delivering justice for victims. The study also examines the obstacles encountered by survivors in obtaining justice, including case underreporting, procedural delays, insufficient institutional support and societal pressure to preserve familial harmony. The article evaluates the strengths and weaknesses of current legal systems, namely Section 498A of the Indian Penal Code and the Protection of Women from Domestic Violence Act, 2005. The paper critically analyzes legal remedies and implementation procedures, revealing the disparity between legislative aim and real enforcement. The article concludes by advocating for legal, institutional and social reforms to bolster victim protection, foster gender sensitivity in the criminal justice system, increase awareness of legal rights and ensure a more effective, victim-centered approach to addressing domestic violence in India.